The diversity of Bryophytes in Nenek Hills, Natural Tourism Park of Mount Permisan, South Bangka Regency - Henri, Henri; Rusidi, Rusidi; Santi, Ratna (Jurnal Biologi Udayana; Vol 25 No 2 (2021): JURNAL BIOLOGI UDAYANADO - 10.24843/JBIOUNUD.2021.v25.i02.p05, 2021)
The mosses growth is generally influenced by temperature, habitat humidity, light intensity, and soil acidity. This study aimed to determine the level of diversity of bryophytes species on various substrates in the Nenek Hills Natural Tourism Park of Mount Permisan, South Bangka Regency. The methods used in this study were exploration and observation. The results of this study are the types of mosses (Bryophytes) found Nenek Hills Natural Tourism Park of Mount Permisan, South Bangka Regency, are from the families Calymperaceae, Dicranaceae, Fissidentaceae, Leucobryaceae, Rhizogoniaceae, Sematophylaceae, Calypogeiaceae, Geocalyceae, Lejeuneaceae, Lepidoziaceae and Plagiochilaceae. The dominating family is Leucobryaceae, Lejeuneaceae and Calymperaceae. The type of substrate that moss prefers to grow is rock. Abiotic factors consist of light intensity with a value of 0,2-7,2 Klx (low), air temperature with a value of 25-29°C (medium-high), humidity with a value of 34-68% (medium-high), soil acidity with a value of 5,9-6,9 (slightly-neutral) and soil moisture with a value of 52-65% (moist).